MEKANISME PENERAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN (CORPORATE SOCIAL RESPONSIBILITY) DALAM KEGIATAN USAHA PERTAMBANGAN - Zsa Zsa Bangun Pratama; Hardi '; Firdaus ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
The existence of the company in the community can provide the positive and negative aspects. The company provides goods and services needed by the community and the work. But on the other hand it is not uncommon to get people from the impact of the company's business activities. Encourage changes in society in order to create a new view on the implementation of Corporate Social Responsibility (CSR). Indonesia, which was awarded the abundant natural resources including minerals mining. The purpose of the study the author wanted to convey in this study: first, know the set corporate social responsibility in Indonesia. Second, know the mechanism of implementation of corporate social responsibility in the mining business.This type of research can be classified in this type of normative research using data sources that comprise the primary legal materials, legal materials and secondary legal materials tertiary.From the results of this study concluded. First, setting the CSR contained in Article 74 of Law No. 40 of 2007 on Limited Liability Companies, Article 15 and Article 34 of Law No. 15 of 2007 on Investment, and Article 2 paragraph (1) of Law No. 19 of 2003 of State Owned Enterprises are packed in the Minister of State Owned Enterprises State No. PER-08/MBU/2013 of Fourth Amendment Regulation of the State Minister for State Owned Enterprises No. PER-05/MBU/2007 about Partnership Program with the State-Owned Enterprises Small Business and Community Development Program, Government Regulation No. 47 of 2012 on Corporate Social Responsibility and Environmental Company Limited, and the Decision of the Constitutional Court of the Republic of Indonesia Number 53/PUU-VI/2008. Second, steps in implementing CSR consists of the identification, planning, preparation, financing, implementation, documentation, auditing and reporting CSR.Keywords: Mechanism - Corporate Social Responsibility - MiningA. PendahuluanKeberadaan perusahaan dalam masyarakat dapat memberikan aspek positif dan negatif. Di satu sisi, perusahaan menyediakan barang dan